Popular culture of Japanese anime in the digital age and the impact on nationalism of young Indonesian citizens - Wisnu Hatami (Universitas Negeri Yogyakarta, 2018)
This research explores the impact of Japanese popular culture in digital era to Indonesia’s young citizen nationalism. Globalization make a life easier, include how to get information. With the digital era, people could get information in another country very fast and the research between globalization and nasionalism growing. This paper based on research of phenomenology about Anime’s Japanese popular culture of Association of Highschool Nihon No Kurabu in Bandung. The amount of informants is twelve and the data collected through interview, observation and documentation study. The result of the research showed that anime’s Japanese popular culture interested informants with the value, character, visual and storyline in that anime. Then, the informants would study about another Japanese popular culture than Indonesia’s traditional cultures.